PENGARUH MODEL PEMBELAJARAN GI-GI (GROUP INVESTIGATION-GUIDED INQUIRY) PADA MATERI SUHU DAN PERUBAHANNYA TERHADAP HASIL BELAJAR DAN KETERAMPILAN PEMECAHAN MASALAH SISWA SMP - Endah Suliasti Ningsih; Supeno Supeno; Nur Ahmad (JURNAL PEMBELAJARAN FISIKA, 2022)
This research aims to examine the effect of the GI-GI (Group Investigation-Guided Inquiry) learning model on the learning outcomes and problem-solving skills of junior high school students in science instruction. The type of research used is quasi-experimental (quasi-research), including quantitative analysis. The research sample was selected using the purposive sampling technique; the samples obtained were class VII B as the experimental class and VII C as the control class from SMP Negeri 3 Rambi Puji. Data collection techniques consist of tests, interviews, and documentation. The data analysis technique of this study used the Independent Sample T-test. The results of this research are the GI-GI (Group Investigation-Guided Inquiry) learning model has a significant effect on the learning outcomes of junior high school students. Furthermore, the GI-GI (Group Investigation-Guided Inquiry) learning model significantly affects the problem-solving skills of junior high school students. Keywords: group investigation-guided inquiry, learning outcomes, problem-solving skills.